2013
DOI: 10.1111/1747-0080.12079
|View full text |Cite
|
Sign up to set email alerts
|

Dietitians' practices and perspectives on nutrition priorities for liver transplant recipients

Abstract: Aim: To describe current practice and priorities of dietitians during the acute (≤3 months) and long-term (≥6 months) management of liver transplant recipients. Methods: Ten liver transplant dietitians (10/14, 71%) in Australia, New Zealand, UK and USA responded to an online survey. The survey graded nutrition priorities on a Likert scale, recorded barriers to service delivery and workforce allocation for nutrition services (ratio of full-time equivalent: annual transplant rate). Results: Just over half (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…On a global scale, the MetS represents a substantial treatment burden due to increased costs and medication expenditure, hospitalization, and utilization of outpatient services [3,4]. The prevalence of the MetS is up to 60% in tertiary health care settings among patients with complex chronic conditions, including kidney and liver disease [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, the MetS represents a substantial treatment burden due to increased costs and medication expenditure, hospitalization, and utilization of outpatient services [3,4]. The prevalence of the MetS is up to 60% in tertiary health care settings among patients with complex chronic conditions, including kidney and liver disease [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that over 40% of kidney dietitians lack adequate time with patients and one in four feel that they do not have appropriate technology and administrative support to implement evidence‐based practice guidelines 11 . Furthermore, where services do exist, they are often fragmented, require individual appointments with multiple healthcare professionals, and are typically restricted to one‐on‐one, face‐to‐face consultations 12–14 . This approach is costly and inefficient and does not adequately meet patient's needs 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, where services do exist, they are often fragmented, require individual appointments with multiple healthcare professionals, and are typically restricted to one‐on‐one, face‐to‐face consultations 12–14 . This approach is costly and inefficient and does not adequately meet patient's needs 12–14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations